MORPHOPHYSIOLOGICAL CHARACTERISTICS WITH THE APPLICATION OF COLLCHICINE IN SOYBEAN (Glycine max (L.) Mer ): KARAKTER MORFOFISIOLOGIS DENGAN APLIKASI KOLKISIN PADA TANAMAN KEDELAI (Glycine max (L.) Mer ) - Wismaroh Saragih , Sanniwati (UPMI Proceeding Series, 2023)
Soybean (Glycine max (L.) Merr) is a very important food commodity as a sourceof vegetable protein whose demand is always increasing in Indonesia. Eventhough Indonesia currently has many superior varieties of soybeans, it is still unable to meet the national demand for soybeans, so it continues to dependonsoybean imports. This problem can be overcome by increasing the quality andproductivity of existing superior soybean varieties through polyploidizationtechniques using colchicine compounds. This study aims to determinethephenotypic and morphophysiological characteristics of colchicine-inducedsoybeans. The phenotypic characters observed were length and width of stomata, plant height, number of pods per plant, number of seeds per plant, weight of 100seeds, flowering age, and soybean maturity. The results showed that theadministration of colchicine based on soybean varieties was successful ininducing polyploidy with colchicine treatment at concentrations of 0.01%and0.02%, and that 10 hours of soaking affected the increase in stomata size, plant height, and weight of 100 seeds in the varieties used. Colchicine also hada significant effect on mealybug attacks and soybean plants were more resistant to lodging.